Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2007
DOI: 10.1145/1240624.1240683
|View full text |Cite
|
Sign up to set email alerts
|

Over-exposed?

Abstract: As sharing personal media online becomes easier and widely spread, new privacy concerns emerge -especially when the persistent nature of the media and associated context reveals details about the physical and social context in which the media items were created. In a first-of-its-kind study, we use context-aware camerephone devices to examine privacy decisions in mobile and online photo sharing. Through data analysis on a corpus of privacy decisions and associated context data from a real-world system, we iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Higher privacy concerns did not lead to an increase of online photo sharing behaviours on Facebook, and neither did it deter them from sharing photos. The results are in line with prior research that has noted the inconsistency between users' privacy concern and their behaviour [17,24,25]. The lack of privacy concern of users was reasoned that the perceived benefits of using the online social networking site and how deeply Facebook has integrated into users' daily routine as an indispensable tool to maintain one's social capital and to maintain communication through technology outweighs the risks of sharing personal content, and users often regarded risk and negative consequences as a third person phenomenon [25].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Higher privacy concerns did not lead to an increase of online photo sharing behaviours on Facebook, and neither did it deter them from sharing photos. The results are in line with prior research that has noted the inconsistency between users' privacy concern and their behaviour [17,24,25]. The lack of privacy concern of users was reasoned that the perceived benefits of using the online social networking site and how deeply Facebook has integrated into users' daily routine as an indispensable tool to maintain one's social capital and to maintain communication through technology outweighs the risks of sharing personal content, and users often regarded risk and negative consequences as a third person phenomenon [25].…”
Section: Discussionsupporting
confidence: 91%
“…In which, research results showed that males are more concerned in regards to their online privacy on Facebook compared to females. Prior research reported that generally there is an inconsistency between users' privacy concerns and their actions [17,20,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Again, this was also the case for the parents surveyed by Ahern et al (2007). While closed-protective and advancedactive users were more likely to have specific rules on posting (or not posting) other people's children's pictures, fence-sitters decided case-by-case.…”
Section: Digital Footprints Privacy and Control: To Post Or Not To mentioning
confidence: 80%
“…From a social science perspective, various studies have explored identity sharing behavior in social network sites and the risk of over exposure of information (notable examples are Refs ). Several studies have shown that users in online environments rely on a variety of cues to make determinations about one another; however, all these cues are not deemed equally credible.…”
Section: Prominent Topics and Approachesmentioning
confidence: 99%